Acetaminophen toxicity induces mitochondrial complex I inhibition in human liver tissue. Issue 1 (4th September 2019) - Chrøis, Karoline Maise; Larsen, Steen; Pedersen, Julie Steen; Rygg, Marte Opseth; Boilsen, Astrid Elisabeth Bruun; Bendtsen, Flemming; Dela, Flemming
Abstract: Acetaminophen (APAP) is used worldwide and is regarded as safe in therapeutic concentrations but can cause acute liver failure in higher doses. High doses of APAP have been shown to inhibit complex I and II mitochondrial respiratory capacity in mouse hepatocytes, but human studies are lacking. Here, we studied mitochondrial respiratory capacity in human hepatic tissue ex vivo with increasing doses of APAP. Hepatic biopsies were obtained from 12 obese patients who underwent a Roux‐en‐Y gastric bypass (RYGB) or a sleeve gastrectomy surgery. Mitochondrial respiration was measured by high‐resolution respirometry. Therapeutic concentrations (≤0.13 mmol/L) of APAP did not inhibit state 3 complex I‐linked respiration. APAP concentrations of ≥2.0 mmol/L in the medium significantly reduced hepatic mitochondrial respiration in a dose‐dependent manner. Complex II‐linked mitochondrial respiration was not inhibited by APAP. We conclude that the mitochondrial respiratory capacity is affected by a hepato‐toxic effect of APAP, which involved complex I, but not complex II.